Manajemen risiko di sektor perbankan indonesia: Tinjauan komprehensif melalui studi literatur - Sadiyah, Nailatus (Maliki Interdisciplinary Journal, 2024)
Supporting the Indonesian economy in the midst of an increasingly complex risk landscape, the role of banks in this regard becomes very important. With rapidly growing risks in both the internal and external environment of the banking sector, along with the increasing complexity of banking operations, there is an urgent need for capable risk management. With this in mind, the researcher conducted a study aimed at studying the landscape of risk management practices in the Indonesian banking sector. This research utilizes literature review to analyze various scholarly articles that have been reviewed. The findings underscore the importance of effective risk management practices across banks in Indonesia, which include both conventional and Islamic institutions. Risks such as reputational, credit, operational, and liquidity were identified as having a major influence on the financial performance and position of banks. Through the implementation of appropriate risk management strategies, banks can manage these risks to uphold financial stability and foster stakeholder confidence.